INNOVATIVE PROCESSES - AS AN IMPORTANT FACTOR IN PRODUCTION DEVELOPMENT - Berdiev Abdumalik, Khakimovich (THE INNOVATION ECONOMY, 2025)
As a result of ongoing economic reforms in our country, the real owners of production enterprises are being formed. However, there is a need to study innovation processes in enterprises and to widely implement the studied innovations into practice. Considering the necessity of enhancing the use of innovations in all branches of industry in the country to increase competitiveness and export potential, the development of modern organizational-economic and management mechanisms plays an important role in addressing these issues